Can Latin America play a more influential role in a shifting world order? - Cattafi, Carmelo; Papp, Robert (Frontiers in Political Science, 2025)
Latin America has played a secondary role in international challenges to a unipolar world order in today’s space for influence in managing the critical challenges transnational security and conflict. This article relations with a focus on Latin America’s role in the relations between Latin America and the great global systemic configuration. So, it analyzes Latin strategic vision, and narratives towards the rest that derive from its economic competition, energy of nearshoring, internal and international security, to the region. Finally, it will attempt to answer the rising impact of the Global South, the influence countries, and political and ideological changes, to play a more important role than in the past.